Delay Modelling at Unsignalized Highway Nodes with Radial Basis Function Neural Networks - Celikoglu, H. B.; Orco, Mauro (Springer Berlin Heidelberg, 2007)
In vehicular traffic modelling, the effect of link capacity on travel times is generally specified through a delay function. In this paper, the Radial Basis Function Neural Network (RBFNN) method, integrated into a dynamic network loading process, is utilized to model delays at a highway node. The results of the model structure have then been compared to evaluate the relative performance of the integrated neural network method.